Extranodal follicular lymphoma in the lung of a free-ranging red deer (Cervus elaphus) - Chang Reissig, Elizabeth (2013)
A hunted free-ranging female red deer (Cervus elaphus) from a region near the Nahuel Huapi National Park, Northern Patagonia, Argentina, had a focally extensive peribronchial lymphoid proliferative lesion in the lung characterized by formation of multiple follicles, with prominent germinal centers lacking mantle zone cells and antigen-related polarity. On examination of immunohistochemically stained tissues, a predominance of B cells (cluster of differentiation [CD]20 positive) with only a few scattered T cells (CD3 positive) were present. The histologic and immunohistochemical characteristics are consistent with follicular lymphoma, which is frequently seen in human beings and less frequently in domestic animals.